Investigation on combined effect of quaternary ammonium compounds and an organic acid on model phospholipid membranes - Vashchenko, O. V.; Pashynska, V. A.; Kosevich, M. V.; Boryak, O. A.; Kasian, N. A.; Lisetski, L. N. (Biophysical Bulletin)
Effects caused by combined inclusion of two membranotropic agents (MTA) of different nature into model phospholipid membranes have been examined. An effect of significant change in activity of individual MTA based on quaternary and bisquaternary ammonium compounds (QAC, BQAC) – decamethoxinum, aethonium, tetramethylammonium – and organic 2,5-dihydroxybenzoic acid (DHB) on their combined incorporation into model multibilayer structures of hydrated dipalmitoylphosphatidycholine (DPPC) is revealed. Differential scanning calorimetry (DSC) data have shown that, when both types of MTA are jointly present in the system, significant deviations from additivity values are noted for the measured calorimetry parameters. This shows that it is the MTA complexes, rather than individual MTAs, affect the model membrane properties. Mass-spectrometric and quantum chemistry calculations data have demonstrated a possibility of formation of stable noncovalent complexes including (di)cations of quaternary ammonium bases and anions of organic DHB acid. Plotting of “membrane melting temperature (Tm) vs. MTA composition” quasi-binary diagrams permitted us to determine the optimal stoichiometry of the BQAC-DHB membrane-incorporated complexes. It was revealed by means of DSC that incorporation into membranes of individual ionic BQAC and DHB as well as their complexes with stoichiometry providing preservation of the ionic (charged) state of the MTAs causes decrease of Tm and, correspondingly, disordering of the membrane structure. At the same time, under MTA concentrations providing neutral complexes of BQAC and DHB, some increase in Tm is observed, corresponding to an ordering of membrane structure, which can be interpreted as deactivation of BQAC, i.e. modulation of their activity in the presence of the organic acid. The ascertained possibility of suppression of membranotropic activity of antimicrobial BQAC on their combined use with an organic acid is to be taken into account in design of multi-component antimicrobial drugs.